MORAL POSITIONING IN THE SOUTH CHINA SEA DISPUTES BETWEEN THE PHILIPPINES AND CHINA - Ramadhani, Eryan (Global: Jurnal Politik Internasional, 2025)
For the past two decades, disputes between the Philippines and China over the South China Sea (SCS) have experienced continuous escalation. Benigno Aquino III filed an arbitration case against China. This legal success was later overturned by Rodrigo Duterte in exchange for closer relations with China. However, his decision did not cease hostility in the SCS. Ferdinand Marcos, Jr. then brought the Philippines back on legal track and steered the country closer to the United States, which further heightened tensions. Built on this background, this article intends to explain the unceasing escalation in the SCS using Positioning Theory (PT). This study finds that both Manila and Beijing used moral positioning under two major themes: maintenance of regional peace and stability and adherence to the rule of law. Positioned as a responsible member of the international community, each side claimed to be the right one while denigrating the other. Such a position was manifested through storylines, and as they unfolded, the social meaning behind moral positioning was revealed. Through the positioning triad―storylines, position, and social meaning―the Philippines and China co-constructed the social realities of the SCS. That neither side acknowledged the other’s positioning made the conflict over the SCS intractable.